Utilization Of Electronic Reminder Method On Enhancement Hazard Reporting Cards In Oil & Gas Company X - Hannisa Yanuar Utama (Sekolah Ilmu Kesehatan Dan Ilmu Alam (SIKIA), Universitas Airlangga, 2021)
Background: Hazard reporting card is a tool used to identify hazards and risks in the workplace. Based on data obtained by researcher, the filling of hazard reporting cards at oil and gas company X, there are only about 30% - 75%, the reason is because employees often forget to fill in, while all employees are required to fill cards every month. Purpose: The purpose of this study is to analyze the possibility of whether the electronic reminder method can be used to increase the number of employee participation in filling out hazard reporting cards. Methods: This study uses a literature review study. Results: The results of the study in 21 journals showed that there were 15 journals successfully applying the reminder method and there were 6 journals stating there were positive responses from respondents towards the application of the electronic reminder method. Conclusion: The conclusion of this research is that this method can be recommended to be applied in the HSE field of the office in the oil and gas company X.